Pengaruh kualitas sistem monitoring anggaran terhadap kepuasan pengguna dan kinerja individual - Kusumo Adi; Deni Mahdiana (Jurnal Kajian Manajemen dan Wirausaha, 2021)
The General Affairs Division of the Secretariat of the Directorate General of Taxes has a Budget Monitoring System to help monitoring budget which is its responsibility in accordance with its duties and functions. However, in its application there are still some features that are deemed insufficient to provide satisfaction to users, thus affecting the individual performance of Budget Monitoring System users. This research aims to determine the effect of system quality, information quality, and service quality on user satisfaction and individual performance in the application of the Budget Monitoring System at the General Affairs Division of the Secretariat of the Directorate General of Taxes using the Delone & Mclean information system success model. The research method used is quantitative. Data collection was carried out using a questionnaire. Research data analysis using Partial Least Square - Structural Equation Modeling (PLS-SEM) using SmartPLS 3.29 software. The results of this research indicate that system quality has no significant effect on user satisfaction, information quality has a significant effect on user satisfaction, service quality has a significant effect on user satisfaction, and user satisfaction has a significant effect on individual performance.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//